Acceleration of Solar Eruptions via Enhanced Torus Instability Driven by Small-scale Flux Emergence - Satoshi Inoue; Takahiro Miyoshi; Keiji Hayashi; Huu Minh Triet Nguyen; Ju Jing; Wenda Cao; Haimin Wang (The Astrophysical Journal Letters, 2025)
Despite decades of research, the fundamental processes involved in the initiation and acceleration of solar eruptions remain not fully understood, making them long-standing and challenging problems in solar physics. Recent high-resolution observations by the Goode Solar Telescope have revealed small-scale magnetic flux emergence in localized regions of solar active areas prior to eruptions. Although much smaller in size than the entire active region, these emerging fluxes reached strengths of up to 2000 G. To investigate their impact, we performed data-constrained magnetohydrodynamic simulations. We find that while the small-scale emerging flux does not significantly alter the preeruption evolution, it dramatically accelerates the eruption during the main phase by enhancing the growth of torus instability, which emerges in the nonlinear stage. This enhancement occurs independently of the decay index profile. Our analysis indicates that even subtle differences in the preeruption evolution can strongly influence the subsequent dynamics, suggesting that small-scale emerging flux can play a critical role in accelerating solar eruptions.